Reconstructing the Chronology of Caesar’s Gallic Wars - Raaflaub, Kurt A.; Ramsey, John T. (Histos, 2017)
Caesar dates only the beginning of his first campaign and rarely mentions routes, distances, and times consumed. No detailed timelines for Caesar’s Gallic Wars exist. This gap can be filled by exploiting available clues in Caesar’s text (e.g., astronomical and seasonal events) and Cicero’s letters, and by determining the routes Caesar is likely to have chosen, average traveling and marching speeds (based on data in Caesar’s works and those of other authors), and the days required to cover the distances involved. Modern, digital maps based upon a GIS interface make it possible to measure distances with unprecedented precision. The resulting chronology, though often still speculative, is much more reliable than anything suggested previously.